A Papertronic, On‐Demand and Disposable Biobattery: Saliva‐Activated Electricity Generation from Lyophilized Exoelectrogens Preinoculated on Paper. Issue 9 (20th July 2017) - Mohammadifar, Maedeh; Choi, Seokheun
Abstract : Portable, on‐demand micropower generation is provided by developing paper‐based biobatteries that can deliver on‐chip energy to the next generation of point‐of‐care (POC) diagnostic platforms. This work creates a low‐cost, disposable, long shelf life and eco‐friendly micropower source that can be easily integrated in paper‐based POC devices and be readily activated by one drop of saliva, which is readily available in any challenging area. A high‐performance, paper‐based, bacteria‐powered battery is created by building microbial fuel cells with inactive, lyophilized (or freeze‐dried) exoelectrogenic cells, allowing for a long shelf life, which generates power within minutes of adding saliva. An oxygen‐tight interface and engineered conductive paper reservoir achieve significant performance boosts from maximized microbial electron transfer efficiency. Exoelectrogenic bacteria preinoculated in the paper battery is freeze‐dried for long‐term storage (in this work, the bacteria cells are stored for up to four months) and can be readily rehydrated for on‐demand power generation. Sixteen microbial fuel cells are incorporated on a single sheet of paper while all are connected in series with two electrical switches mounted on a paper circuit board, which produce more than enough electrical energy to power an on‐chip, light‐emitting diode. Abstract : A portable, on‐demand micropower source is demonstrated by building paper‐based microbial fuel cells with inactive, lyophilized exoelectrogenic cells. Exoelectrogenic bacteria preinoculated in the paper battery is freeze‐dried for long‐term storage and can be readily rehydrated by saliva for on‐demand power generation. An oxygen‐tight interface and engineered conductive paper reservoir achieve significant performance boosts from maximized microbial electron transfer efficiency.